2006
DOI: 10.1152/ajpheart.00651.2005
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nrf2/ARE pathway protects endothelial cells from oxidant injury and inhibits inflammatory gene expression

Abstract: The antioxidant response element (ARE) is a transcriptional control element that mediates expression of a set of antioxidant proteins. NF-E2-related factor 2 (Nrf2) is a transcription factor that activates ARE-containing genes. In endothelial cells, the ARE-mediated genes are upregulated by atheroprotective laminar flow through a Nrf2-dependent mechanism. We tested the hypothesis that activation of ARE-regulated genes via adenovirus-mediated expression of Nrf2 may suppress redox-sensitive inflammatory gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
253
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(267 citation statements)
references
References 46 publications
12
253
1
1
Order By: Relevance
“…Moreover, nrf2 knockout mice showed prolonged inflammation during cutaneous wound healing (31) and displayed enhanced bronchial inflammation and susceptibility to severe airway inflammation and asthma (32,33). The Keap1/Nrf2/ARE pathway has also been shown to modulate redox-sensitive inflammatory gene expression in endothelial cells (34). Also in Nrf2-deficient mouse embryonic fibroblasts exposed to both inflammatory cytokines INF-␥ and TNF-␣, we observed that the Keap1/Nrf2/ARE pathway is essential for the anti-inflammatory effects of triterpenoids (19).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nrf2 knockout mice showed prolonged inflammation during cutaneous wound healing (31) and displayed enhanced bronchial inflammation and susceptibility to severe airway inflammation and asthma (32,33). The Keap1/Nrf2/ARE pathway has also been shown to modulate redox-sensitive inflammatory gene expression in endothelial cells (34). Also in Nrf2-deficient mouse embryonic fibroblasts exposed to both inflammatory cytokines INF-␥ and TNF-␣, we observed that the Keap1/Nrf2/ARE pathway is essential for the anti-inflammatory effects of triterpenoids (19).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress induces NQO1 expression as a defense system [14]. Endogenous antioxidant systems have been shown to suppress the expression of redox-sensitive inflammatory genes such as monocyte chemoattractant proteins (MCP)-1 and vascular cell adhesion molecules (VCAM)-1 [7,15]. In addition, the atheroprotective properties of laminar shear stress are mediated through NQO1 expression, and thus NQO1 appears to be important in protecting vessels against oxidative stress and atherogenesis [4,7,15].…”
Section: Discussionmentioning
confidence: 99%
“…10,27,28 AREregulated gene transcription has been shown to be a central mechanism providing protection against oxidative stress in the cardiovascular system. [29][30][31] Oxidized low density lipoprotein and 15d-PGJ 2 , agents that are important in vascular inflammatory processes such as atherogenesis and are present in atherosclerotic lesions, 22,32 are also potent instigators of ARE activation, 17,33 suggesting that vascular inflammatory processes could be targets for ARE-regulated gene therapy. In addition, in I/R injury, activation of Nrf2 during reperfusion mediates cytoprotective gene expression, 34 implying that ARE-regulated vectors could also be used for attenuation of reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%